The Degree of Epistemic Modality in Poe’s the Murders in the Rue Morgue and its Indonesian Translation - Fransiska Dewi Hastuti (Journal La Sociale, 2024)
The epistemic modality in detective story helps to build the mysterious atmosphere since its linguistic feature deals with the speaker’s assessment toward the assumptive truth. Readers of detective stories can be captivated by the uncertainty and probability that hinder them from uncovering the truth until the stories end. Thus, this research aims to describe the degree or value of epistemic modality in Poe’s The Murders in the Rue Morgue and its Indonesian equivalent. A descriptive translation approach is used, and a comparative analysis is employed in this research toward the source and target texts. The results show that the modal markers of low degree dominate the English original story, and of the high degree are for the Indonesian translation. However, consistency in translating the degree of epistemic modality is shown by the domination of similar value combination: High-High, Median-Median, and Low-Low. Meanwhile, the types of modal markers presenting the degree of epistemic modality are similarly used in both English and Indonesian versions of the story, except for the relational attributive clause. The English epistemic modality mostly happens in form of positive modal auxiliaries (46.8%) and the Indonesian Epistemic markers are dominated by modal adverbs (27.7%).